Health behavior and aging on patients with the acute pancreatitis - Lubecka, Hanna; Haor, Beata (Pielęgniarstwo w Opiece Długoterminowej / Long-Term Care Nursing, 2018)
Introduction Most people with acute pancreatitis are between 41 and 60 years old. Among the factors contributing to the onset of the disease are the anti-health behaviors. Aim The aim of the study was to present the health behavior of patients with acute pancreatitis according to sociodemographic variables that may influence the course of the aging process. Material and methods The study was conducted among 50 people with diagnosed acute pancreatitis. The study used the estimation method, the estimation technique using the Health Behavior Inventory. Results Patients affected with acute pancreatitis exhibited an average level of health behavior that was differentiated according to selected sociodemographic variables. Conclusions Age-related effects have been shown to have a higher level of health behavior in patients with acute pancreatitis.